A Study on the Exclusion of Graduates of Church Oriented Theological Institutions from NYSC in Nigeria: A Case Study of Selected Theological Institutions of Higher Education - John Arierhi Ottuh (SOCIETIES: Journal of Social Sciences and Humanities, 2021)
Abstract. The continuous exclusion of Church oriented theological institutions’ (COTI) graduates from the National Youth Service Corps (NYSC) in Nigeria calls for concern in theological education as an aspect of higher education. The important role NYSC plays in the life of a graduate in Nigeria is a veritable prove that COTI graduates need the NYSC for their future endeavours. The main objective of the study is to determine whether there is the exclusion of COTI graduates from the NYSC. Therefore, using the retrospective approach as a method, two theological institutions, one each representing Northern and Southern Nigeria were selected as case study for a retrospective analysis within the period of 9 years (2008-2017). The result showed that for the past nine years, out of the 1917 graduates from both Theological College for Northern Nigeria and Baptist Theological Seminary, Eku, none (99.9%) was mobilized for NYSC or exemption. A survey conducted subsequently revealed that one of the major reasons for such exclusion was due to non-accreditation by Government institution of higher education. The paper recommends that the present existing accreditation structure be collapsed for an all embracing accreditation structure that will have the capacity of accrediting all qualified tertiary institutions in Nigeria. Keywords: Exclusion, Higher education, graduates, Church Oriented Theological Institution, Accreditation